THE SIGNALS TREATMENT ALGORITHM FOR SATELLITE RADIO NAVIGATIONAL EQUIPMENT CONSUMERS INTENDED TO PROVIDE A PRECISION APPROACH TO THE RUNWAY IN CONDITIONS OF RADIO INTERFERENCE IMMUNITY - G. V. Krinitskiy (Научный вестник МГТУ ГА)
Currently, a number of countries widely implemented the landing aircraft system according to the signals of satellite navigation systems (SNS), providing the approach for category I, and the research and development in the area of improvement to ensure the approach categories II and III are actively conducted, they impose higher requirements on  such characteristics as accuracy and reliability. An approach to the runway and landing are very crucial stages of flight, therefore, the necessity of high reliability landing systems are required with the help of SNS signals. Due to the fact that the SNS consumer equipment interference immunity (SNS CE), in which there are no special measures for protection from noise and the provision of maintenance at low levels of the received signals is extremely low, so the navigational equipment is becoming easy targets for terrorist, sabotage and vandalism actions due to its simplicity and compactness of the device jamming for SNS. In addition, due to the continuous expansion of the use of various radio communication facilities, the risk of emergence of the interference immunity of the SNS consumer equipment increases, caused by spurious emissions of radio communication means during their operation or as a result of their disfunction. The algorithm of signals’ treatment in ground and onboard radio navigational equipment designed to ensure a precise landing approach with the help of SNS signals is suggested. The mathematical modeling of the algorithm during the conditions of signals multipath distribution was held.